(untitled) (Sport Science Research, 2025)
This article presents a comprehensive review of scientific data on the effects of the ovarian‑menstrual cycle (OMC) phases on the physiological status, adaptation to training loads, and competitive performance of female athletes, with a focus on combat sports (judo, women’s wrestling, jiu‑jitsu, boxing). The mechanisms of hormonal fluctuations and their influence on aerobic and anaerobic capacity, strength characteristics, recovery, and perceived performance are examined. Results from clinical studies and systematic reviews highlighting both controversial and consistent effects of the OMC on athletic performance are analyzed. Practical implications for coaches and athletes are discussed, along with perspectives for further research in the physiology of female athletes in combat sports.